The concentration of polyphenolic compounds and trace elements in the Coffea arabica leaves: potential chemometric pattern recognition of coffee leaf rust resistance - Silva, Francisco L.F.; Nascimento, Gerlan O.; Lopes, Gisele S.; Matos, Wladiana O.; Cunha, Rodrigo L.; Malta, Marcelo R.; Liska, Gilberto Rodrigues; Owen, Robert; Trevisan, M. Teresa S. (Food research international, 2020)
Coffee (Coffea arabica L.) is an important commodity, involving about 500 million people from the cultivation of the coffee trees to final consumption of infusions of the ground roasted coffee beans. In contrast to a considerable amount of research performed on green coffee beans, there are relatively few studies regarding the chemical constituents of coffee leaves. Hemileia vastatrix is a parasite, specific to coffee plants and causes coffee leaf rust, which is a very destructive disease. Some coffee plants have natural resistance which is mainly linked to a gene and specific host resistance response. An increase in flavonoid production may be related to fungal disease resistance, with the levels and flavonoid types being an early physiological response to rust infection. Trace inorganic elements can be related to many roles in the defense response of higher plants and can be used as a biomarker for some diseases. To address this, coffee leaves from 16 different cultivars of Coffea arabica were harvested from Minas Gerais, Brazil (susceptible and resistant to rust) and their polyphenolic compounds were extracted using the QuEChERS technique and quantitated by HPLC-ESI-MS. The same leaves were decomposed using an acid mixture in a block digester and the content of Al, Cu, Mg, Mn, Ni, Sn and Zn was quantitated by ICP-OES. Principal component analysis (PCA) was applied and we could establish a relation between polyphenolic and trace element concentration in the leaves with resistance to rust infection. On this basis in this preliminary study we were able to separate the resistant from the susceptible cultivars. The main compounds responsible for this differentiation were the content of chlorogenic acid and magnesium in the leaves. The content of polyphenolic compounds was lower in susceptible cultivars and a diametric effect was observed between Mn and Mg concentrations. This study shows potential for the discrimination of resistant and susceptible coffee trees based on the analyses of both trace element and polyphenolic concentration.
Gesehen am 20.07.2020